Sekep dalam Tradisi Madura Muslim di Desa Bandang Laok Kecamatan Kokop Kabupaten Bangkalan - Siti Juraiyah; Wasid (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2020)
Abstract: The article reveals the popular Sekep tradition in Bangkalan, Madura. The focus of this research includes: 1) How did Sekep originate; 2) What values are contained in Sekep; 3) The efforts of Bandang Laok village in preserving Sekep. The approach and theoretical framework used for this research is the Historical and Anthropological approach, for the theory using Clifford Geertz on Cultural Interpretation. While the method used is cultural research with qualitative methods, using descriptive data analysis techniques, from the results of interviews, field notes, and documentation. From the results of this study it can be concluded that the origins of the Sekep Tradition date back to the time of the Madura kingdom in 1296M in the form of heirlooms, and were known by the Madurese in the 18th century, a hero figure Pak Sakera who always carried a sickle everywhere. Then it was preserved by the people of the Blater tribe, as well as a symbol of the identity of the Madurese people. From its development, the Sekep Tradition has declined from time to time and is almost extinct due to the modernization era, only a few communities still preserve the Sekep Tradition. Keywords: traditioni, Madura, Muslim, history